A study on factors affecting employee’s job satisfaction at Malaysian Qualifications Agency (MQA) / Syed Afifi Sayed Abd Rahman - Sayed Abd Rahman, Syed Afifi (2014)
This research was carried out to examine the factors affecting the job satisfaction at Malaysian Qualifications Agency (MQA). Job satisfaction in employees seems to be declining even though there are continues initiative to help them by giving them training and development to improve the quality of employee’s performance to achieve organization success. In present organizational culture, job satisfaction has emerged into organizational performance and become its major component. Job satisfaction can represent the moral of employees in carrying their task, duties and responsibilities and it directly affect their performance. The question arises thus, why exactly job satisfaction might be decline year by year. The scope of research is focusing on three factors affect the job satisfaction in employees are pay factor, working conditions and workload. This study involved 120 employees excluded high position in Malaysian Qualifications Agency (MQA). The instrument used in this research was a set of questionnaires. The findings of this study indicate pay factor, working condition and workload show how the factors affect toward job satisfaction. The entire factors have a significant correlation relation with job satisfaction. Based on the findings, the researcher recommends to organization (Malaysian Qualifications Agency (MQA) using this research as reference to improve employee’s job satisfaction and continue this for future research.